The Role of Post Occupation Evaluation in Achieving High Performance Buildings through Diagnostics. (2017) - Munsami, Krishna; Prasad, Deo; Ding, Lan
Abstract: Buildings are major consumers of energy for heating and cooling. The number of buildings is growing rapidly with demand for energy. To reduce consumption, governments worldwide have implemented codes, standards, and building practices. In New South Wales, Australia the planning department introduced a web-based energy-modelling tool intended to increase the thermal performance of the residential building's envelope prior to development applications. The modelling tool, Building Sustainability Index (BASIX) was introduced in 2004. Building codes and standards in them selfs are not perfect instruments but guidelines to achieve building objectives. However, there is evidence in literature stating that buildings are not achieving the predicted results in thermal performance leading to increased energy consumption. This research looks into the predicted modelling aspects to the BASIX program for thermal performance and undertaking a diagnostic study in verifying the building envelope meeting its objectives. This study considered the building envelope the key factor in thermal performance, in which building practices may undermine codes and standards delivering sub-optimal performance. The research justifies the need for diagnostics as a tool to evaluate building practices in reducing the performance gap between the modelled and the delivered results. This would provide building professionals, and government bodies in understanding and addressing the cause of performance gaps between the predicted and actual results for thermal performance in future buildings.